Effects of international contractors involvement in construction project / Ernie Aryanee Sapiyan - Sapiyan, Ernie Aryanee (UITM Sarawak,Kampus Samarahan, 2019)
International contractor is a contractor that resides in other target market in different country. In Malaysia, international contractors' involvement can be seen in some of the mega project in Malaysia. However, there are issues by local contractors where they are risk in become subcontractors, lack financial capabilities, advance technology and competitiveness among contractors. Therefore, with the aim of this research to study the effects of international contractors' involvement in construction project in Sarawak, three objectives had been secured. There are to study the involvement of international contractors in construction industry, to gauge the issues and benefits encounter by international and local contractors in construction project and to analyse the effects of international contractor's involvement in construction industry. The method of data collection to be used is quantitative data which is questionnaire. SPSS software is used to produce statistics for the data analyzed. The type of data analysis to be used in this dissertation are reliability test, descriptive analysis and cross tabulation. The findings shows that majority of local contractors aware on the influences of international contractor in the construction industry and economic development but the least involved in project joint venture with them. Apart from that, the research also reveals that international contractors has contributes in terms of skills and expertise and technology transfer in local construction industry whereby the least are in economy and innovation. Lastly, the involvement of international contractors' has resulted on the effects of construction market becoming tougher and the least is in terms of price factor. For conclusion, in accordance of rapid development of the country, the government should implements more initiatives to increase the level of competitiveness among local contractor in line with accelerating industrialization, growth and modernization of the country.